Alloionema californicum Nermuť, Půža, Mráček & Lewis, 2016 is a junior synonym of Alloionema similis Holovachov, Boström, Tandingan De Ley, Mc Donnell, Alvarado, Paine & De Ley, 2016 (Nematoda: Alloionematidae) - Nermuť, Jiří; Holovachov, Oleksandr; Ley, Irma Tandingan De; Půža, Vladimír (Zootaxa, 2017)
The genus Alloionema (Rhabditida: Alloionematidae) currently includes three nominal species—the type species, Alloionema appendiculatum, and two recently described species: A. similis and A. californicum. Comparison of morphological, molecular and ecological characters demonstrates that A. similis and A. californicum belong to the same species, providing support for their synonymization, as proposed in this publication.